Chromosomal mapping of the mink cell focus-inducing and xenotropic env gene family in the mouse. - Blatt, C (1983)
Chromosomal locations of members of the xenotropic-related env gene family in the mouse genome have been determined. Endonuclease restriction site polymorphisms detected by molecular hybridization were used to study the inheritance of mink cell-focus inducing and xenotropic env gene-related sequences in recombinant inbred strains of mice. Some of the endogenous env sequences appear to be closely linked to genes determining leukemia virus induction and to genes involved in the immune response, such as the heavy and light chains of the immunoglobulin molecules or allotypic determinants on B and T lymphocytes. The use of probes that detect restriction fragment length polymorphisms in a small family of dispersed sequences promises to yield a large number of markers that can be used together with recombinant inbred strains for efficient mapping of the mouse genome.